Perancangan Augmented Reality (AR) Book Dasar Komputer pada Mata Pelajaran Informatika Kelas X TJKT 2 di SMK Negeri 1 Pandeglang - Mutaqin, Reihan; Dayurni, Popi; Ismatullah, Ismatullah (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
This research aims to develop an Augmented Reality (AR) Book for the Informatics subject for class X students of the TJKT 2 class at SMK Negeri 1 Pandeglang, with the goal of improving the quality of learning, which has previously been conducted in a conventional manner. The research method used is Research and Development (RnD) with the Multimedia Development Life Cycle (MDLC) model, which consists of six stages: concept, design, material collection, assembly, testing, and distribution. The validity of this AR Book was assessed by subject matter experts and media experts, yielding very satisfactory results, with averages of 93.78% and 94.67%, respectively. This AR Book on Basic Computer Skills has proven to have high levels of validity, practicality, and effectiveness, making it an efficient learning tool to support Informatics education in vocational schools.